Subcutaneous Fat Biopsy to Diagnose Secondary Amyloidosis in patients with Rheumatoid Arthritis - Cucho Venegas, Mariano (1999)
OBJECTIVE: To detect secondary amyloidosis (AA) in patients with rheumatoid arthritis (RA). MATERIAL AND METHODS: We assayed length of disease, extraarticular involvement, functional ability, anatomical compromise, white cell count, erythrocyte sedimentation rate, rheumatoid factor (RF) (latex test), serum albumin, and urine analysis. All of patients underwent periumbilical aspirate of subcutaneous fat. Samples were stained with Congo red, and light microscopy and polarized microscopy were used. Green-apple birefrigence was taken as AA (+). RESULTS: We studied 81 patients with RA (ACR criteria), 71 of them were females. The ages were between 31 and 80 years. 75/81 patients were RF (+), 3/81 were AA (+). Average length of disease was 14,74 years in AA (-) patients and 20,3 years in AA (+). Just one patient showed renal deposits of amyloid. CONCLUSION: Our occurrence of amyloidosis in patients with AR was lower. Patients with secondary amiloidosis and AR had higher RF levels and larger length of disease.